Early versus late acute coronary syndrome risk patterns of coronary atherosclerotic plaque . (29th July 2022) - van den Hoogen, Inge J; Stuijfzand, Wijnand J; Gianni, Umberto; van Rosendael, Alexander R; Bax, A Maxim; Lu, Yao; Tantawy, Sara W; Hollenberg, Emma J; Andreini, Daniele; Al-Mallah, Mouaz H; Cademartiri, Filippo; Chinnaiyan, Kavitha; et al.
Abstract: Aims: The temporal instability of coronary atherosclerotic plaque preceding an incident acute coronary syndrome (ACS) is not well defined. We sought to examine differences in the volume and composition of coronary atherosclerosis between patients experiencing an early (≤90 days) versus late ACS (>90 days) after baseline coronary computed tomography angiography (CCTA). Methods and results: From a multicenter study, we enrolled patients who underwent a clinically indicated baseline CCTA and experienced ACS during follow-up. Separate core laboratories performed blinded adjudication of ACS events and quantification of CCTA including compositional plaque volumes by Hounsfield units (HU): calcified plaque >350 HU, fibrous plaque 131–350 HU, fibrofatty plaque 31–130 HU and necrotic core <30 HU. In 234 patients (mean age 62 ± 12 years, 36% women), early and late ACS occurred in 129 and 105 patients after a mean of 395 ± 622 days, respectively. Patients with early ACS had a greater maximal diameter stenosis and maximal cross-sectional plaque burden as compared to patients with late ACS ( P < 0.05). Larger total, fibrous, fibrofatty, and necrotic core volumes were observed in the early ACS group ( P < 0.05). Findings for total, fibrous, fibrofatty, and necrotic core volumes were reproduced in an external validation cohort ( P < 0.05). Conclusions: Volumetric differences in composition of coronary atherosclerosis exist between ACS patients according to their timing antecedent to the acute event. These data support that a large burden of non-calcified plaque on CCTA is strongly associated with near-term plaque instability and ACS risk. Graphical Abstract: Graphical Abstract Early versus late ACS risk patterns of coronary atherosclerotic plaque. Schematic representation of the study design and patients (left panel), specifics of the two cohorts (middle panel), and the volumetric differences in composition of coronary atherosclerosis between patients with early versus late ACS (right panel). ACS, acute coronary syndrome; CCTA, coronary computed tomography angiography; MACE, major adverse cardiac events.